Institutional requirements for market-led development in Latin America - Cimoli, Mario...[et al.] (ECLAC SantiagoCL, 2003)
Seeks to provide a systematized framework for the main ideas that have been developed by ECLAC concerning the effects that market-led reforms have had on labour, financial and technology markets.